Ecological Studies : Analysis and Synthesis - Billings Durham,W D (Ecological Studies 38,25,47, 1981)
1.Ecology of a Salt Marsh : Pomeroy,L R , Wiegert,R G 2.Pollutants in Porous Media : Yaron,B , Dagan,G , Goldshmid,J 3.Microbial Ecology of a Brackish Water Environment : Rheinheimer,G